Foraging behaviour of medfly larvae is affected by maternally transmitted and environmental bacteria. (January 2022) - Sivakala, Kunjukrishnan Kamalakshi; Jose, Polpass Arul; Shamir, Maayan; C-N Wong, Adam; Jurkevitch, Edouard; Yuval, Boaz
Abstract : Multicellular organisms are intimately associated with a variety of microorganisms, which exert significant biological effects on their hosts. In this study, we tested the hypotheses that medfly, Ceratitis capitata (Diptera: Tephritidae) larvae orient towards bacteria and that this response can be modulated by the symbiotic state of the larvae and by its microbial exposure experience. To do so we examined the responses of first-instar axenic (i.e. bacteria-free) and symbiotic (i.e. with native bacteria) medfly larvae to individual colonies of several bacterial species known to be either beneficial ( Pectobacterium carotovorum, Pectobacterium sp., Klebsiella oxytoca, Klebsiella pneumoniae, Providentia vermicola ) or potentially harmful to the flies ( Pseudomonas aeruginosa and Staphylococcus pasteuri) . Beneficial bacteria were significantly more attractive to symbiotic than to axenic larvae, while S. pasteuri was not attractive to either group. When presented with a choice between two bacterial isolates, larval choice was significantly affected by their symbiotic state, pre-exposure to bacteria and the bacterial species involved in the choice. Specifically, P. aeruginosa and S. pasteuri were universally shunned, while symbiotic and axenic larvae differed in their response to the other isolates. Axenic larvae travelled significantly longer distances than the symbiotic larvae and larval movement increased significantly when bacterial cues were present in the arena. We suggest that our findings reflect a dynamic and plastic interaction between bacteria and larvae that leads to adaptive foraging decisions. Highlights: Bacteria significantly and specifically affect foraging behaviour of medfly larvae. Larvae are attracted to commensal bacteria, while pathogens are shunned. Manipulation of the microbiome affects these patterns.